Geometric Evaluation of Bends: Systematic Literature Review on Suitability to Driver Safety - Wandhani, Intannia; Rifatunnisa, Rifatunnisa; Lasti, Silpi Naskah; Hendrayana, Yayat; Handayani, Susanty (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Road safety issues on curves are a significant concern in reducing traffic accidents in Indonesia. Roads like the Cibatu–Sidamukti route have sharp bends that pose serious risks, worsened by natural factors (heavy rain, slippery surfaces) and inadequate infrastructure (lack of signage, poor road conditions, ineffective drainage). Additional risks come from poor lighting and undisciplined driver behavior. This study highlights the importance of addressing curve-related hazards by examining technical (road geometry, surface quality, signage, markings, lighting) and non-technical (driver behavior, vehicle condition) causes of accidents. Using a literature review method, the study analyzes scientific articles, journals, and books to build a strong theoretical foundation and identify research gaps. The primary focus is evaluating curve geometry's suitability for driver safety, especially in tourist areas with high accident potential. This evaluation is intended to support recommendations for road design improvements and the implementation of necessary safety measures. The findings are expected to serve as valuable input for local governments and stakeholders to improve road safety.